Analysis of interest expense deduction in transfer pricing dispute in Indonesia - Nasikhudin, Nasikhudin; Supriyadi, Supriyadi (WIM Solusi Prima, 2024)
This study provides a comprehensive examination of interest expense disputes within the context of transfer pricing in Indonesia. Multinational enterprises frequently employ transfer pricing mechanisms to reduce their tax obligations, often leading to legal challenges in tax courts. The research employs a qualitative methodology, focusing on a detailed analysis of several tax court verdicts related to interest expense disputes. The primary dataset comprises appellate verdicts available from the official tax court repository. The study identifies key factors influencing the outcomes of such disputes, including the strength of the evidence presented, the consistency between recorded contracts and actual economic conditions, coherence between transfer pricing documentation and real-world practices, the legitimacy and rationality of the loan arrangements, utilization of reliable comparability data, and substantive arguments concerning the applicability of the Debt-to-Equity Ratio (DER) for assessing interest expense reasonableness. Furthermore, the research underscores crucial considerations for taxpayers, such as the role of DER in determining expense reasonableness, the regulatory framework governing interest-free loans, methodologies for applying the arm’s length principle in interest expense transactions, and the importance of meticulous documentation in transfer pricing files (TP Documentation).